Marketing and Supply Chain Management of Perishable Products (Trinity Journal of Management, IT & Media (TJMITM), 2011)
This paper analyses the problem and designs the supply  chain management for perishable products. The  challenges for managing these products in that: their  value deteriorates over time in the supply at the rates  that are highly temperature and humidity dependent.  Mismanagement supply chain destroys these products.
Keywords: Supply chain strategy; Responsiveness; Efficiency; Speed; Business chain input - logistics; Flexibility; delivery time; Transports tion